1996
DOI: 10.1007/bf00714336
|View full text |Cite
|
Sign up to set email alerts
|

Preferential uptake of long chain polyunsaturated fatty acids by isolated human placental membranes

Abstract: Fatty acid uptake by the placenta is thought to be a carrier-mediated process, however the mechanism by which long chain polyunsaturated fatty acids (LCPUFA) are preferentially accumulated from the maternal circulation to the fetal tissues is still unclear. To examine the role of the placenta in this process, binding of four different radiolabelled fatty acids (-14C-oleate, -14C-linoleate, [14C]a-linolenate and [14C]arachidonate) to human placental membranes was studied. Binding of fatty acid was found to be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 36 publications
6
57
0
1
Order By: Relevance
“…The enhanced proportion of these fatty acids in cord blood plasma in contrast to the limited placental transfer for saturated fatty acids as compared to PUFA (Campbell et al, 1996;Haggarty et al, 1997) would indicate an active lipogenesis in the fetus, as demonstrated in previous studies (Dunlop & Court, 1978). Similar reasoning could be used to justify the high proportion of oleic acid in cord blood plasma, although slightly lower than in the mothers during late gestation.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The enhanced proportion of these fatty acids in cord blood plasma in contrast to the limited placental transfer for saturated fatty acids as compared to PUFA (Campbell et al, 1996;Haggarty et al, 1997) would indicate an active lipogenesis in the fetus, as demonstrated in previous studies (Dunlop & Court, 1978). Similar reasoning could be used to justify the high proportion of oleic acid in cord blood plasma, although slightly lower than in the mothers during late gestation.…”
Section: Discussionsupporting
confidence: 54%
“…Similar reasoning could be used to justify the high proportion of oleic acid in cord blood plasma, although slightly lower than in the mothers during late gestation. Placental transfer of oleic acid is also lower than that of PUFA (Campbell et al, 1996;Haggarty et al, 1997), and therefore its proportional abundance in the fetus may reflect an active desaturation of stearic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Arachidonate is also an important precursor for lipid signaling molecules. Since LC-PUFA are synthesized in insuf®cient quantity by the fetus, and the placenta apparently does not possess the D5 and D6 desaturase activities to convert essential fatty acids to LC-PUFA (reviewed in Crawford, 1993;Campbell et al, 1996), mechanisms for the preferential synthesis and transfer of these fatty acids to the fetus and placenta must be in place. Since these mechanisms are at the core of the most important questions concerning lipid metabolism in pregnancy, the focus of this discussion will be the problem of providing LC-PUFA to the fetus.…”
Section: Introductionmentioning
confidence: 99%
“…The ®rst is the presence of a plasma membrane fatty acid binding protein (FABP PM in Figure 1). FABP PM was identi®ed in human and sheep placenta by Campbell et al (1996) and the order of preference for the four fatty acids studied was arachidonic ) linoleic ) a-linolenic b b b b b oleic acid. Trans fatty acids inhibited the binding ef®ciently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation